Comparative assessment of the quality of life of the patients after phacoemulsification of cataract, complicated by a violation of capsular support of the lens, with various methods of fixation of the posterior chamber intraocular lens - Kozhukhov A.A; Kapranov D.O. (РМЖ "Клиническая офтальмология")
Kozhukhov A.A.1, Kapranov D.O.2 1 Clinic «Medline-service», Moscow 2 City Clinical Hospital №13 of Avtozavodsky District, Nizhny Novgorod Aim: to perform a comparative assessment of the quality of life (QOL) of the patients after phacoemulsification (FEC), complicated by a violation of capsular support of the lens, with various methods of fixation of the posterior chamber intraocular lens (PC-IOL). Patients and Methods: 174 FECs were analyzed according to the standard procedure. The patients were divided into three groups equivalent by the age and degree of maturity of the cataract - the main group (MG, 56 eyes), in which the IOL was sutured by an original technique, according to which the ends of the filaments were fixed in the corneal layers, and two control groups, where IOL was fixed under the scleral flap (K1, 58 eyes) and to the iris (K2, 60 eyes). The QOL was assessed before and one month after the operation by the questionnaires «VFQ-25», «Questionnaire for assessing the quality of life of patients with cataracts» («QQLPC») and questionnaire «Quality of Visual Life» («QVL»). Results: the most pronounced increase of QOL according to « QQLPC», «QVL», «VFQ-25» was noted in the MG (94.7, 25.7 and 9.9%), in the K1 group, the positive dynamics were less pronounced (86.8, 14.6, 7.0%), in the K2 group even less pronounced (85.3, 12.3, 6.7%). Conclusion: the developed original method of fixation (in layers of the cornea) of the PC-IOL after FEC, complicated by the violation of capsular lens support, provides a higher level of QOL of the patient, compared with the traditional methods of fixation (to the iris, under the scleral flap) (on average, according to three applied questionnaires on 7.3-8.6%), while the most pronounced differences (by 11.1-12.3%) are determined by the high refractive results of the operation. Key words: phacoemulsification of cataract, intraocular lens, capsule of the lens. For citation: Kozhukhov A.A., Kapranov D.O. Comparative assessment of the quality of life of the patients after phacoemulsification of cataract, complicated by a violation of capsular support of the lens, with various methods of fixation of the posterior chamber intraocular lens. RMJ “Clinical ophthalmology”. 2018;2:81–84.